The French language spoken in Cameroon : an analysis of four discourse markers (là, par exemple, ékyé et wèé) - (:unkn) unknown (My University, 2016)
This thesis sets out to describe and to analyse the discourse markers (DMs) là, par exemple, ékyé and wèé in Cameroon French, a regional variety of French that is spoken in Subsharan Africa. It is a pragmatic study of oral discourses that highlights how communication is based on speech inter-subjectivity such as DMs, which constitute linguistic traces. In order to study these uninvestigated pragmatic phenomena in Cameroon spoken French, three notions were of prime necessity, namely: discursive continuity, social implicity and interaction. These notions help to shed light on the informational structure and on the situational context of the DMs là, par exemple, ékyé and wèé in discourse organization as well as in its production or in its reception. The data of this study was got from two sources: on the one hand, radio programmes, and on the other hand, scripts collected from the internet. The study comprises two parts: Part one focuses on the theoretical concerns, alongside some illustrations of excerpts from the data. The second part provides a systematic analysis of the data (the functioning of the four DMs là, par exemple, ékyé and wèé in radio programmes and in internet scripts). This analysis enabled the confirmation that not only is it difficult to clearly define what a DM is but that there are also several competing terms and explanations, as theories regarding studies on DMs are heterogeneous. We propose an operational definition of DMs for the analysis of the data and suggest that studies on regional French spoken in Africa should take into account oral phenomena related to interaction.
Keywords: African Research